Bell's locality condition confronting perfect anti-correlations - Nowakowski, M. [UNESP] (Elsevier, 1999)
We show that Local Realistic Theories, defined as obeying the Bells's locality condition, cannot satisfy the prefect anti-correlations without at the same time maximally violating rotational symmetry at the hidden variable level. We examine whether the rotational symmetry can be restored after the statistical average. We also comment on the question whether such theories are necessarily deterministic at the hidden variable leva. © 1999 Elsevier Science B.V. All rights reserved.